Grace Banker and her Hello Girls answer the call : the heroic story of WWI telephone operators - Friddell, Claudia (Calkins Creek, an imprint of Boyds Mills & Kane, 2021)
"Led by twenty-five-year-old Grace Banker, thirty-two telephone operators -- affectionately called Hello Girls back in the US -- became the first female combatants in World War I. Follow Grace Banker's journey from her busy life as a telephone switchboard trainer in New York to her pioneering role as the Chief Operator of the 1st Unit of World War I telephone operators in the battlefields of France. With expert skill, steady nerves, and steadfast loyalty, the Signal Corps operators transferred orders from commanders to battlefields and communicated top-secret messages between American and French headquarters. After faithfully serving her country--undaunted by freezing weather and fires; long hours and little sleep, and nearby shellings and far off explosions--Grace was the first and only woman operator in the Signal Corps to be awarded the Army's Distinguished Service Medal."--Provided by publisher.